21.9k views
0 votes
4(2x - 1) + 3 When x=6

Evaluate


User Vaness
by
5.1k points

2 Answers

7 votes

Answer: 47

Concept:

Here, we need to understand the idea of evaluation.

When encountering questions that gave you an expression with variables, then stated: "If x = a, y = b, z = c" (a, b, c are all constants), this means you should substitute the value given for each variable back to the expression.

Solve:

Given information

x = 6

Given expression

4 (2x - 1) + 3

Substitute values into the expression

=4 [2 (6) - 1] + 3

Simplify by multiplication

=4 (12 - 1) + 3

Simplify by subtraction

=4 (11) + 3

Simplify by multiplication

=44 + 3

Simplify by addition

=
\boxed{47}

Hope this helps!! :)

Please let me know if you have any questions

User Lendrick
by
4.3k points
3 votes

Answer:


4(2x - 1) + 3 = 8x - 4 + 3 \\ = 8(6) - 4 + 3 \\ = 48 - 4 + 3 \\ = 47

I hope I helped you^_^

User Lihao
by
4.9k points